ANALISIS HUKUM TERHADAP PEMBATALAN AKTA PERDAMAIAN SECARA SEPIHAK (STUDI KASUS PUTUSAN PERKARA PERDATA NO: 605/Pdt.G/2013/PN.Mdn) - IRVEB IMANUEL TARIGAN (PREMISE LAW JURNAL, 2016)
The unilateral annulment made before a Notary was actually unnecessary to be made again because the Court Ruling has contained the legal force to annul the deed. The Notary is not authorized to make an annulment deed of reconciliation as stipulated in Article 1338 paragraph (2). The legal consequences produced after the Ruling No.605/Pdt.G/2013/PN.Mdn were that the Agreement Deed No.08 dated February 21, 2012 and Reconciliation Agreement Deed No.09 dated February 21, 2012 were annulled By The Law. Based on the conclusion, it is suggested that the parties involved in the making of the deed of reconciliation agreement be assisted by a mediator. It is also suggested that all parties who make the agreement of reconciliation concur and comply with the requirements mentioned by the law, in this case the Article 1320 of the Civil Code. It is recommended that the Notary be more conscientious in making the Deed of Reconciliation and pay more attention to the provisions and regulations in the prevailing Law, so that any kind of potential conflict can be prevented in the future. Keywords: Reconciliation Deed Annulment, Unilaterally, Ruling